A formação na sociedade do espetáculo: gênese e atualidade do conceito - Maria Luiza Belloni (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
The text revisits the proposals of Guy Debord and his companions of the Internationale Situationniste, seeking to highlight its revolutionary character, which makes critical use, in a radically creative manner, of the most important tools of the spectacle, the media, since it is they which produce its image. The article seeks to contextualise the appearance of the most notable theoretical contribution of Guy Debord, the concept of spectacle as a social relation and of the spectacle society, whose actuality is undeniable. Recuperated by the media so strongly criticised by Debord, the concept entered into common usage which proves the success of the idea: society was becoming so spectacular that the concept of spectacle imposed itself as a proof for the understanding of contemporary societies.